A study of knowledge, attitudes and practices (KAP) of a rural community on malaria and the mosquito vector. - Ongore, D.; Kamunvi, F.; Knight, R. (East African medical journal, 1989)
A study of malaria on the Kano Plain, Kisumu District, Western Kenya, was carried out between April and August, 1985. The study included a knowledge, attitudes and practices (K.A.P.) survey on malaria illness and the mosquito vector. Overall knowledge about malaria illness was found to be good. However, treatment and prevention practices of malaria were found to be poor. Knowledge of the mosquito and its relationship to malaria was found to be high. Knowledge of methods of prevention of mosquito bites was also found to be high but actual use of the methods was low. Knowledge of traditional methods of prevention of mosquito bites was also found to be high. Actual use was again found to be low.
Keywords: Study; knowledge, attitudes and practices; Rural community; Malaria and the mosquito vector